Pengaruh Kualitas Produk, Persepsi Harga, Dan Kualitas Pelayanan Terhadap Keputusan Pembelian Pada Kedai Kopi Konnichiwa - Sandra, Tsania Junia; Prawoto, Prawoto (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2024)
This study aims to assess the influence of product quality, price perception, and service quality both partially and simultaneously on purchasing decisions for Konnichiwa coffee. The research method utilizes a quantitative approach involving 130 samples selected intentionally (purposive sampling), while data collection is conducted through questionnaire distribution using the Google Form platform. Â Data processing involves assessing validity, reliability, T-tests, and F-tests. The analysis results indicate that product quality significantly influences purchasing decisions, with a significance level of 0.027. Meanwhile, perceptions of price and service quality also have a very significant influence on purchasing decisions, with a significance value of 0.000. Keywords: product quality; price perception; service quality; buying decision